Sustainable Landscape Construction: Materials and Products — Plastics and Rubber - Gail Hansen (EDIS, 2010)
ENH1149, a 1-page fact sheet by Gail Hansen, describes the environmental concerns, design strategies, and construction techniques for using plastics and rubber in landscape construction. Includes references. Published by the UF Department of Environmental Horticulture, October 2009.